HUBUNGAN PANJANG BERAT DAN FAKTOR KONDISI IKAN SEPENGKAH (Parambassis wolffi) DI SUNGAI ROKAN, PROVINSI RIAU - Dwirastina, Mirna (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
Sepengkah (Parambasis wolffi) is a member of order Perciformes, family Chandidae. This research was aimed to determine the relationship of length and weight and condition factor of sepengkah (Parambasis wolffi). The study was conducted from March to October 2011 in Sungai Rokan Kepulauan Riau. The result showed that a length-weight relationship of Sepengkah was positive allometric (b = 3,264) where the weight  is faster grow than the length. The condition factor of Sepengkah was around 3,2-4,0, it was showed that the body of Sepengkah was close to flat. Key words : fish length , fish weight , condition factor , Ikan Sepengkah , Rokan River